2017
DOI: 10.21608/japp.2017.7494
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Test and Anastomosis Group of Rhizoctonia solani the Causal Organism of Stem Canker and Black Scurf Disease of Potato in Egypt

Abstract: Stem canker and black scurf caused by Rhizoctonia solani Kuhn is considered the most destructive disease and reduce productivity of potato. Pathogenicity test of 12 isolates of R. solani obtained from two governorates, ElSharkiya (New El-Salhia region) and Ismailia (El-Shabab region) revealed that all isolates were pathogenic, however isolate No.RS7 was the most virulent isolate in the development of the stem canker and black scurf disease. Molecular technique using PCR applied to determine anastomosis group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…4). This result agrees with the findings of Abdel-Sattar et al, (2017). The sequence of the isolates was submitted to the National Center for Biotechnology Information (NCBI), GenBank and gave accession numbers (MZ267232, MZ267234 and MZ267689), respectively.…”
Section: -supporting
confidence: 90%
See 1 more Smart Citation
“…4). This result agrees with the findings of Abdel-Sattar et al, (2017). The sequence of the isolates was submitted to the National Center for Biotechnology Information (NCBI), GenBank and gave accession numbers (MZ267232, MZ267234 and MZ267689), respectively.…”
Section: -supporting
confidence: 90%
“…Rhizoctonia isolates differed among themselves in severity of the infection, although similar conditions, this is an indication of the role in different virulence (Rubio et al, 1996). Abdel-Sattar et al, (2017) stated that virulence of isolates in pathogenicity attributed to the difference between R. solani Anastomosis groups (AGs).…”
Section: -Virulence Evaluation Of R Solani Isolatesmentioning
confidence: 99%
“…Pathogenicity test of 12 isolates showed significant differences between isolates where RS7 was the most virulent isolate in the development of the stem canker and black scurf disease on potato cv. 'Spunta' in Egypt (Abdel-Sattar et al, 2017). R. solani isolates, even under similar conditions, showed significant differences in infection severity and induced symptoms, suggesting the involvement of genetic factors in virulence differences (Rubio et al, 1996).…”
Section: Preliminary Pathogenicity Testmentioning
confidence: 95%
“…R. solani isolates, even under similar conditions, showed significant differences in infection severity and induced symptoms, suggesting the involvement of genetic factors in virulence differences (Rubio et al, 1996). Variance of isolates in pathogenicity was also attributed to difference between (AGs) where R. solani AGs, other than AG3, usually have low virulence against potato (Balkana and Wenham, 1973;Yanar et al, 2005;Khandaker et al, 2011;Abdel-Sattar et al, 2017). Jaradat et al (2023) showed that R. solani AG-3PT was the primary pathogen associated with potato stem canker and black scurf diseases in Jordan.…”
Section: Preliminary Pathogenicity Testmentioning
confidence: 99%
“…R. solani isolates, even under similar conditions, showed significant differences in infection severity and induced symptoms, suggesting the involvement of genetic factors in virulence differences (Rubio et al, 1996). Variance of isolates in pathogenicity was also attributed to difference between (AGs) where R. solani AGs, other than AG3, usually have low virulence against potato (Balkana and Wenham, 1973;Yanar et al, 2005;Khandaker et al, 2011;Abdel-Sattar et al, 2017). Jaradat et al (2023) showed that R. solani AG-3PT was the primary pathogen associated with potato stem canker and black scurf diseases in Jordan.…”
Section: Preliminary Pathogenicity Testmentioning
confidence: 99%